Web of paradox. - Thorburn, David (American Prospect)
The writer discusses the metaphors associated with the use of World Wide Web and the Internet and related technology. He states that such metaphors implicitly celebrate motion, activity, acquisition, and the conquest of space, and he points out that it is deeply instructive that such swashbuckling metaphors should define the basically sedentary experience of sitting at a computer terminal with a mouse and keyboard. He considers the contradiction or dissonance between the celebratory, heroic metaphors and the physical, moral, and intellectual actualities of computer use. He acknowledges, however, that from the aspect of continuity or history, it is possible to recognize that the supposedly unique and central aspect of experience with the World Wide Web reenacts a distinctive joining or blurring of true and false, connection yet isolation, and public yet private that is also at the root of peoples' experience of film, television, and even books.